WAVE OVERTOPPING ACTING ON BACKFILL STONE AND GEOTEXTILE SHEET OF CAISSON TYPE SEAWALLS - SUZUKI, Kojiro; SHIMOSAKO, Kennichiro; KURODA, Toyokazu; OHKI, Yasunori (PROCEEDINGS OF CIVIL ENGINEERING IN THE OCEAN, 2001)
The recent utilization of reclaimed land to provide large-area, man-made islands, e. g., those used for airports, has necessitated their construction in relatively deep seas, which naturally requires them to be surrounded by seawalls that are directly exposed to strong waves since no protective breakwaters are present. Consequently, failures frequently occur during and after construction. Especially, the breakage of backfill stone and geotextile sheet, which caused by wave overtopping and transmitting wave through rubble mound during the construction, result in landusage problems and expensive long-term maintenance requirements. We conducted a hydraulic experiment in order to investigate the breakage mechanism caused by wave overtopping. The pressures and velocity acting on the part of backfill stones and geotextile sheet are measured. The impulsive pressures and consequent transmitting waves acting on the slope of backfill stones lead to the breakage of geotextile sheet and collapsing of backfill stones.